PERILAKU IMPULSIVE BUYING GENERASI Z: GAYA HIDUP DAN MEDIA SOSIAL DI KOTA MEDAN - Aryesha Putri; Ernita; Firdaus Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the influence of lifestyle and social media on impulsive buying among Generation Z in Medan City. A quantitative approach was employed using purposive sampling with 97 respondents. Data were analyzed using multiple linear regression with IBM SPSS Statistics. The results show that lifestyle has a positive and significant effect on impulsive buying (Sig. = 0.001), social media has a positive and significant effect on impulsive buying (Sig. = 0.000), and both variables simultaneously have a significant effect on impulsive buying (F = 35.517; Sig. = 0.000). The coefficient of determination (R² = 0.430) indicates that lifestyle and social media explain 43% of the variation in impulsive buying, while 57% is influenced by other factors. The findings support the Theory of Planned Behavior and provide implications for digital marketing strategies and future research.